Mapping excellence in teacher education: The role of centers of excellence in teacher quality - Leih Maruss V. Sinsay-Villanueva; Glenda Darlene V. Garcia; Valerie L. Lim; Ivan Harris Tanyag; Jenard D. Berroya; Aniceto C. Orbeta; John Paolo R. Rivera (Philippine Institute for Development Studies (PIDS), 2025)
As part of the reforms introduced following the first Congressional Commission on Education (EDCOM) in 1994, the Teacher Education Council (TEC) was tasked with identifying and establishing Centers of Excellence (COEs) in teacher education in the Philippines, before it was relegated to the Commission on Higher Education (CHED) in 2007. The primary goal of this initiative was to enhance the quality of both pre-service and in-service teacher education through the evaluation of specific parameters outlined by the TEC. Previous studies have highlighted that parameters such as teacher qualifications are significant contributors to student performance in basic education. This study examines the role of COEs/CODs in maintaining the quality of teacher education more than two decades after this arrangement was first introduced. Specifically, it investigates the benefits and challenges associated with these designations, the measures these centers have taken to fulfill their responsibilities, and their potential role in supporting underperforming teacher education institutions (TEIs) and regions. A mixed methods approach was employed in this study, combining desk research, key informant interviews, and focus group discussions. Using triangulation, several research themes emerged regarding the nature and dynamics of COEs/CODs. One major finding suggests disparities in the regional distribution of these centers, attributed to the stringent compliance requirements. While some intended benefits of these centers remain unclear, they have nonetheless inspired non-COE/COD institutions in their respective regions. The study concludes with a series of actionable recommendations aimed at guiding policymakers in effectively implementing, maintaining, and sustaining these centers nationwide.
Keywords: 330; teacher education; teacher quality; mapping; centers of excellence; centers of development